Therapeutic Management of Acute Pancreatitis in Three Dogs - Venkatesh, Atmakur; Sumathi, Devaraju; Mohanambal, Kaliyannan; Kavithakumari,, Umesh Gupta; Ravi, Ramasamy; Swamy , Kallipatti Karupusamy Ponnu (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The pancreas is a tubuloalveolar gland (Watson, 2015)  situated in the right cranial quadrant caudal to the  stomach, composed of a left limb or lobe, which lies behind  the greater curvature of the stomach and adjacent to the  cranial aspect of the transverse colon; a right limb or lobe  which lies just medial to the proximal duodenum and a body  between these two limbs. It is composed of two types of  cells responsible for endocrine and exocrine functions. The  major function of the exocrine pancreas is the production,  storage, and secretion of digestive enzymes important for the  degradation of ingested proteins, fats, and polysaccharides  which are subsequently released into the stomach and/or  small intestine as food reaches these organs. The digestive  enzymes produced by the pancreatic acinar cells are stored  until the pancreas is stimulated to secrete them into the  duodenum. Acute pancreatitis typically presents as a  sudden, sterile inflammation marked by necrosis and edema.  This condition does not cause permanent damage to the  pancreatic structure and is entirely reversible. It is believed  that acute pancreatitis arises mainly due to the improper  activation of zymogens within the pancreas, leading to  autodigestion, inflammation, and tissue necrosis. This  document reports successful therapeutic management of  acute pancreatitis in three dogs.
Keywords: degradation; adjacent